Faktor-Faktor yang Mempengaruhi Perubahan Deposito Mudharabah (Studi Empiris Pada Bank Umum Syariah di Indonesia) - Jannah, Dinna Miftakhul; Fitrijanti, Tettet; Adrianto, Zaldy (IAIN Kudus, 2020)
This study aims to examine the factors influencing the changes of mudharabah deposit in Islamic banks in Indonesian during the period of 2014-2018. The dependent variable used in this research is mudharabah deposit in the Islamic bank. The independent variable in this research is financing to deposit ratio (FDR), nonperforming financing (NPF), bank size, interest rate, and rate of return is moderating variable. The sample used in this study is all Islamic Commercial Banks in Indonesia in 2014-2018. The data analysis method used in this study is panel data regression analysis and moderated regression analysis. The results showed that simultaneously financing to deposit ratio, nonperforming financing, bank size, interest rate, and rate of return is moderating variable influenced mudharabah deposit. The results showed that partially financing to deposit ratio and bank size have a significant positive effect on mudharabah deposits. Nonperforming financing variable and interest rates have no significant effect on mudharabah deposits. The rate of return variable as a moderating variable has no significant effect relationship between the interest rate and mudharabah deposits.